Charge Transfer in Ternary Solar Cells Employing Two Fullerene Derivatives: Where do Electrons Go?. Issue 7 (21st October 2021) - Sperlich, Andreas; Auth, Michael; Dyakonov, Vladimir
Abstract: Earlier reports demonstrated that ternary organic solar cells (OSC) made of donor polymers (D) blended with different mixtures of fullerene acceptors (A : A) performed very similarly. This finding is surprising, as the corresponding fullerene LUMO levels are slightly different, which might result in decisive differences in the charge transfer step. We investigate ternary OSC (D : A : A) made of the donor polymer P3HT with stoichiometric mixtures of different fullerene derivatives, PC60 BM : PC70 BM and PC70 BM : IC60 BA, respectively. Using quantitative electron paramagnetic resonance (EPR) we can distinguish between positive and negative polarons, localized on the specific molecules. We found that after the initial charge transfer step, the electrons are re‐distributed over two nearby acceptors in agreement with their stoichiometry and their relative LUMO energy difference. Remarkably, the measured ΔLUMO differences in fullerene mixtures are reduced by an order of magnitude compared to that of the pristine materials, i. e., below 1 meV for PC60 BM : PC70 BM and (20±5) meV for PC70 BM : IC60 BA. Furthermore, we found that this reduced ΔLUMO explains the shift in open circuit voltage for D : A : A organic solar cells. We attribute these findings to hybridization, leading to an effective fullerene LUMO. Consequently, multi‐acceptor blends are indeed a viable option for photodetectors and solar cells, as they combine the best electron acceptor and light absorbing properties. Abstract :